Jarisch Herxheimer Reaction in an Adolescent with Secondary Syphilis: A Case Report - S, Jain; L, Mohapatra; P, Mundada; P, Raj (Journal of Pharmacy Practice and Community Medicine)
The Jarisch-Herxheimer reaction is defined as a transient immunological reaction, classically seen in patients during antimicrobial treatment of syphilis. Clinically, it manifests within 24 h with short-term constitutional symptoms (fever, chills, headache, myalgia) and exacerbation of existing cutaneous lesions. Herein, we present a case of Jarisch-Herxheimer reaction in an adolescent.
Keywords: Jarisch-Herxheimer reaction; Syphilis; Adolescent; Immunological reaction; Antimicrobial treatment.